2018
DOI: 10.1172/jci70712
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the aryl hydrocarbon receptor/polyamine biosynthesis axis suppresses multiple myeloma

Abstract: Polyamine inhibition for cancer therapy is, conceptually, an attractive approach but has yet to meet success in the clinical setting. The aryl hydrocarbon receptor (AHR) is the central transcriptional regulator of the xenobiotic response. Our study revealed that AHR also positively regulates intracellular polyamine production via direct transcriptional activation of 2 genes, ODC1 and AZIN1, which are involved in polyamine biosynthesis and control, respectively. In patients with multiple myeloma (MM), AHR level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 114 publications
(178 reference statements)
3
35
1
Order By: Relevance
“…4a). Similar results were observed using clofazimine, a recently described antagonist of the AHR 31 , and KYN-101, an optimized, selective synthetic antagonist of AHR (Supplementary Fig. 6a).…”
Section: Ahr Expression Is Associated With Immunosuppression In Humansupporting
confidence: 82%
See 1 more Smart Citation
“…4a). Similar results were observed using clofazimine, a recently described antagonist of the AHR 31 , and KYN-101, an optimized, selective synthetic antagonist of AHR (Supplementary Fig. 6a).…”
Section: Ahr Expression Is Associated With Immunosuppression In Humansupporting
confidence: 82%
“…Clofazimine was prepared in a solution of 5% DMSO in PBS and mice were treated with daily i.p. injections at 10 mg/kg as described 31 . Epacadostat was dissolved in a 0.5% MC vehicle solution and 680C91 in a 5% DMSO + 5% Solutol solution in water and administered daily by oral gavage at 300 mg/kg and 20 mg/kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the AhR active drugs, such as tranilast, flutamide or omeprazole, might be effective chemotherapeutics for the treatment of breast and pancreatic cancers [7]. An anti-leprosy Food and Drug Administration (FDA)-approved drug and AhR antagonist clofazimine suppressed multiple myeloma in transgenic mice [8]. Targeting of AhR with antagonists was suggested as a strategy for delaying the relapse during the treatment of melanoma with vemurafenib [9] or for inhibiting constitutive AhR activity in prostate cancer [10].…”
Section: Introductionmentioning
confidence: 99%
“…Traces of environmental pollutants can be discovered throughout the world in a variety of sources, including the air, water, soil. Clinical studies have shown that these environmental carcinogens are toxic to the body by binding to AhR and cause cancer in many tissue types, especially the prostate and breast (Bianchi-Smiraglia et al 2018;Yu et al 2018).…”
mentioning
confidence: 99%